Reducing stress among new boarding school students: The impact of Al-Qur'an reading intensity analyzed through expert systems and PHP - Musyandi, Angga Zulfa; Dahrul, Annida; Handayani, Ruri; Syahti, Maghriza Novita; Lindriani, Nofita; Huda, Azizatul (Utan Kayu Publishing, 2024)
This study investigates the impact of Al-Qur'an reading intensity on stress reduction among new students at Insan Scholar Boarding School, utilizing an expert system and PHP methods. Employing an experimental design and quantitative data analysis, this study compares stress levels before and after the implementation of an intensive Quran reading intervention. The data collection instrument uses a psychological scale, namely the DASS stress scale (Depression Anxiety own scale) adapted from the character lovibond & lovibond. Results indicate a significant decrease in stress levels among participants engaged in Quran reading activities compared to those who did not participate. These findings underline the importance of spiritual practices in stress management and suggest integrating Quran reading activities into mental health programs in educational environments. The study offers new insights into the application of spiritual methods alongside information technology to support students' psychological well-being, contributing significantly to stress management practices in similar educational settings. The implications of this research emphasize the need to recognize and integrate the spiritual dimension as a crucial component in stress reduction programs, as well as the potential for information technology applications to facilitate spiritual activities.